Effectiveness of Community-Based Exercise Interventions in Fall Prevention in the Elderly: A Systematic Review - Aris Widiyanto; Hanung Prasetya; Rubiyanta (Journal for Quality in Public Health, 2026)
Falls in older adults are a major public health problem associated with increased morbidity, disability, decreased quality of life, and healthcare burden. Community-based exercise interventions have been widely implemented to reduce fall risk among older adults living in the community. This systematic review aimed to analyze the effectiveness of community-based exercise interventions in preventing falls among older adults. The review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Literature searches were performed in PubMed, Scopus, ScienceDirect, ProQuest, and CINAHL databases for articles published between 2019 and 2024. Inclusion criteria included primary studies with randomized controlled trial or quasi-experimental designs involving community-dwelling older adults receiving exercise-based interventions. Six studies met the inclusion criteria and were analyzed using narrative synthesis. The interventions included Lifestyle-integrated Functional Exercise (LiFE), Tai Chi-based exercise, multicomponent exercise, balance training, and home safety intervention. The findings showed that community-based exercise interventions effectively reduced fall risk, improved balance, mobility, physical activity, and decreased fear of falling among older adults. Multifactorial interventions combining exercise, education, and home safety assessment demonstrated more optimal outcomes than single interventions. Community-based exercise programs can be considered effective promotive and preventive strategies for fall prevention in older adults.